Efficiency-oriented phased urban green space planning framework to mitigate heat-stress exposure - Zhiwei Yang; Jian Peng (npj Urban Sustainability)
Abstract Extreme heat events intensified by climate change and urbanization are heightening population exposure to heat-stress (heat-stress exposure). Although urban green spaces (UGS) offer an effective countermeasure, most planning ignores planning-efficiency, i.e. heat-stress exposure covered per unit area of additional-UGS (UGS planned for construction). We introduced an efficiency-oriented UGS planning framework that reconstructed hourly thermal comfort data (Universal Thermal Climate Index, UTCI), coupled these data with dynamic population data to map heat-stress exposure, linked extracted cooling-zones to UGS size to simulate the cooling performance of additional-UGS, and ranked additional-UGS by planning-efficiency (Lorenz curve). Applied to Kunming’s urban core, the framework identified 783 additional-UGS patches whose cooling-zones intersected 9.14 × 106 person·°C of heat-stress exposure (23.7% of the total). Ranking additional-UGS by planning-efficiency and segmenting the Lorenz curve produced five priority levels: planning in only Priority 1 (around 10% of additional-UGS area) would cover nearly 40% of coverable heat-stress exposure, while Priority 1 + 2 (around 32%) would cover over 86%. These findings demonstrate that accurate augmentation, phased expansion of high planning-efficiency UGS, can achieve greater cooling benefits with limited land, offering a transferable tool for urban heat resilience planning.